Correlation of PK/PD Indices with Resistance Selection for Cefquinome against Staphylococcus aureus in an In Vitro Model - Li, Yafei; Feng, Baoyi; Gu, Xiaoyan; Yang, Dawei; Zeng, Zhenling; Zhang, Bingxu; Ding, Huanzhong (Frontiers in Microbiology, 2016)
Cefquinome is a fourth-generation Cephalosporin approved for use in animals exclusively. The objective of this study was to explore the relationship of cefquinome pharmacokinetic/pharmacodynamic (PK/PD) indices with resistance selection of Staphylococcus aureus ATCC25923 in an in vitro model. Six dosing regiments of cefquinome at an interval of 24 h for three consecutive times were simulated, resulting in maximum concentrations (Cmax) from 1/2 MIC to 16 MIC and half-lives (t1/2β) of 3 and 6 h, respectively. The in vitro sensitivity of S. aureus was monitored by bacterial susceptibility and dynamic time-kill curve experiments over the six cefquinome concentrations. The correlation between changes in bacterial susceptibility (MIC72/MIC0) and the percentage of time within mutant selection window (MSW) versus dosing interval (TMSW %) was subjected to Gaussian function and regression analysis. The results favored the consensus that time above MIC (T>MIC) was recognized as an important PK/PD parameter of cephalosporins for antibacterial efficiency. Cefquinome reached the maximum killing effect when T>MIC% attained approximately 40%~60%. The subsequent correlation analysis demonstrated that resistant S. aureus ATCC25923 was easy to occur when TMSW% attained an index of about 20% with t1/2β of 3 h after multiple dosing, and 40% with t1/2β of 6 h after multiple dosing.